Misreading in the Name of Companions of Prophet Mohammad - Ramezan Mohammadi (تاریخ اسلام)
Misreading-tashif- being interpreted as an alteration in the dots and letters of a word while keeping its original structure is one of the corruptions of written sources which is also noticeable in the sources of history of Islam. It is included a numerous samples of misreading in the name of companions of Prophet Mohammad in the sources related to them as well as the Prosopography’ books and the ignorance of them leads to some difficulties in the comprehension of historical propositions concerning the life of prophet. Investigating the sources of Prosopography, this writing has tried to study the reasons of misreading and its varieties in the name of companions and to clarify the denotations of misreading, moreover, following the consideration of consequences of misreading in the comprehension of the life of prophet; it proposes the ways of identification of misreading to the researchers.